Laser-induced crystallization of anodic TiO2 nanotube layers. Issue 37 (9th June 2020) - Sopha, Hanna; Mirza, Inam; Turčičova, Hana; Pavlinak, David; Michalicka, Jan; Krbal, Milos; Rodriguez-Pereira, Jhonatan; Hromadko, Ludek; Novák, Ondřej; Mužík, Jiří; Smrž, Martin; Kolibalova, Eva; et al.
Abstract : Laser treatment of amorphous TiO2 nanotube layers leads to their crystallization without deformation or formation of the thermal oxide layer. Abstract : In this study, crystallization of amorphous TiO2 nanotube (TNT) layers upon optimized laser annealing is shown. The resulting anatase TNT layers do not show any signs of deformation or melting. The crystallinity of the laser annealed TNT layers was investigated using X-ray diffraction, Raman spectroscopy, and high-resolution transmission electron microscopy (HRTEM). The study of the (photo-)electrochemical properties showed that the laser annealed TNT layers were more defective than conventional TNT layers annealed in a muffle oven at 400 °C, resulting in a higher charge recombination rate and lower photocurrent response. However, a lower overpotential for hydrogen evolution reaction was observed for the laser annealed TNT layer compared to the oven annealed TNT layer.